Lithium cobalt oxide positive electrode material and preparation method and application thereof
By doping Mg-Y-Zr into the core layer of the lithium cobalt oxide positive electrode material and forming a spinel fast ion layer of Co-Al-Ti-O and Li-Co-F lithium composite, the problems of irreversible structural evolution and interface deterioration of lithium cobalt oxide positive electrode material under high voltage are solved, and long cycle stability and electrochemical performance improvements are achieved at high voltage and high temperature.
Patent Information
- Application Number
- CN202411560083.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Lithium cobalt oxide cathode material faces irreversible structural evolution and interface deterioration under high voltage, resulting in attenuation of battery electrochemical performance.
By doping Mg-Y-Zr to the core layer, a spinel fast ion layer of Co-Al-Ti-O is formed, and a Li-Co-F lithium composite is formed on the outer layer of the shell, and the structure and interface are coordinated to improve conductivity and suppress side reactions at the interface under high voltage.
The stability of lithium cobalt oxide positive electrode material in high voltage (4.55V) and high temperature is achieved, and the electrochemical performance and cycle life of the battery are improved.
Smart Images

Figure CN119092695B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy, and in particular to a lithium cobalt oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] As the cathode material of high-end consumer lithium-ion batteries, the development of lithium cobalt oxide (LCO) is closely related to the battery life of consumer electronic products. Lithium cobalt oxide (LCO) has a high theoretical capacity of 274mAh / g, but the current commercial market mainly uses 4.45V LCO products, and its actual capacity is 180 mAh / g, which only reaches 66% of its theoretical capacity.
[0003] Increasing the charge cut-off voltage is the most effective technical strategy to improve the discharge capacity and energy density of LCO. However, when the charge cut-off voltage (≥4.55 V) is increased, the structural destruction and interface degradation of LCO will be accelerated, resulting in rapid capacity decay and power loss. During the charging process, multiple phase changes will occur as lithium ions are released, resulting in poor reversibility of the structural transformation; at the same time, the activity of the material lattice oxygen will become higher and higher, resulting in oxygen evolution and cobalt dissolution; the violent side reactions when charged to high voltage will lead to the accumulation of interface by-products. LCO faces irreversible structural evolution and interface degradation problems under high voltage, which will deteriorate the electrochemical performance of the battery, and ultimately lead to the decay of the battery's electrochemical performance, which is more obvious at high temperatures.
[0004] In order to solve the above problems, the applicant has previously filed the following application: CN118458839A, the subject of which is a coated modified lithium cobalt oxide positive electrode material and a preparation method thereof, and a lithium ion battery, which discloses that the doping element is at least one of titanium, magnesium, aluminum, zirconium, and yttrium; the coating element is at least one of zirconium, yttrium, cobalt, lanthanum, and aluminum;
[0005] Meanwhile, the publication No. CN116768282B, the subject of which is a high-temperature high-rate lithium cobalt oxide and its preparation method, discloses the steps of doping the lithium cobalt oxide core layer, using one or more of cobalt compounds, titanium-containing compounds, and aluminum-containing compounds for the first coating, and using nano fast ion conductors and fluorides for the second coating;
[0006] It discloses that nano fast ion conductors reduce material impedance, improve high temperature performance and rate performance, and increase surface stability of particles; after being modified by fluoride coating, the cycling and high temperature storage performance under high voltage are significantly improved, and irreversible phase change and gas production are also effectively suppressed.
[0007] Under high voltage, the stability of the core layer, the side reactions on the surface, and the conductivity are several very critical parameters. It can be seen from the above literature that everyone is constantly trying to solve one or more of the above problems through different methods.
[0008] The technical problem solved in this case is: how to further improve the stability of the core layer, reduce the side reactions on the surface, and improve the conductivity of the lithium cobalt oxide positive electrode material. Summary of the invention
[0009] The object of the present invention is to provide a lithium cobalt oxide positive electrode material, which stabilizes the thermal stability of the lattice structure of LCO under high voltage by doping Mg-Y-Zr in the core layer, forms a fast ion layer with the spinel phase of Co-Al-Ti-O in the shell layer, and improves the conductivity of LCO; the Li-Co-F lithium composite in the outer layer of the shell provides a part of the capacity while isolating the direct contact between the lithium cobalt oxide and the electrolyte, inhibits the occurrence of side reactions at the interface under high voltage, and coordinates the structure and interface to achieve long-cycle lithium cobalt oxide at high voltage (4.55V) and high temperature.
[0010] At the same time, the present invention also provides a preparation method and application of the lithium cobalt oxide positive electrode material.
[0011] The specific scheme of the present invention is:
[0012] A lithium cobalt oxide positive electrode material, comprising a core layer, a shell layer, and a protective layer arranged in sequence from the inside to the outside;
[0013] The core layer is a core layer made of lithium cobalt oxide doped with Mg, Y and Zr;
[0014] The shell layer is a fast ion layer of spinel phase composed of Co, Al, Ti and O elements;
[0015] The protective layer is a lithium composite layer composed of Li, Co and F elements.
[0016] In the present invention, Mg-Y-Zr is doped in the core layer to stabilize the thermal stability of the lattice structure of LCO under high voltage, and the spinel phase of Co-Al-Ti-O in the shell layer forms a fast ion layer to improve the conductivity of LCO; the Li-Co-F lithium composite in the outer shell layer provides a part of the capacity while isolating the direct contact between lithium cobalt oxide and the electrolyte, inhibiting the occurrence of side reactions at the interface under high voltage, and the structure and interface are synergistically regulated to achieve long-cycle lithium cobalt oxide at high voltage (4.55V) and high temperature.
[0017] More specifically, in the core layer, Mg, Y, and Zr elements are doped to improve the relatively stable structure of the positive electrode material, the purpose of which is to improve the stability of the core layer during the subsequent fast ion layer preparation process;
[0018] The fast ion layer of the spinel phase needs to be prepared by a wet method. If Mg, Y, and Zr elements are not doped, its interface structure is prone to collapse, which ultimately manifests itself in deteriorated cycle performance.
[0019] The spinel phase of Co-Al-Ti-O of the present invention forms a fast ion layer, which needs to be prepared by a wet method. Compared with the traditional dry mixing and calcining method, it can form a stable fast ion layer, improve conductivity, and facilitate the release and entry of lithium ions. At the same time, the shell structure is stable, which improves the cycle stability under high voltage conversion;
[0020] The lithium composite layer of the present invention provides a part of the capacity and isolates the direct contact between lithium cobalt oxide and the electrolyte, thereby inhibiting the occurrence of side reactions at the interface under high voltage and maintaining the stability of the cycle performance.
[0021] In the above-mentioned lithium cobalt oxide positive electrode material, the core layer contains 0.135-0.305 wt % of magnesium oxide, 0.055-0.165 wt % of yttrium oxide and 0.055-0.165 wt % of zirconium oxide, which is equivalent to 0.135-0.305 wt % of the weight of lithium cobalt oxide.
[0022] Compared with single doping, Mg-Y co-doping can improve the cycle performance, and Mg-Y-Zr co-doping can further improve the cycle performance. Y has a larger ion radius, which can increase the diffusion channel of lithium ions and is beneficial to the transmission of lithium ions. Mg and Zr doping can play a "pillar role", reduce lattice distortion, stabilize crystal structure, and improve conductivity.
[0023] In the above-mentioned lithium cobalt oxide positive electrode material, the molar ratio of Al element to Ti element in the fast ion layer is 0.9-2.7:0.5-1.55.
[0024] The highly conductive Li-Co-Al-Ti-O layer is conducive to the conduction of Li+ and resists the corrosion of electrolytes. During the cycle process, the introduction of strong Al and Ti─O bonds and the introduction of surface recombination areas stabilize the lattice oxygen near the surface, thereby hindering the formation of oxygen vacancies and the occurrence of harmful phase changes. A small amount of Al and Ti co-modification does not change the structure of the coating layer and cannot form a fast ion conductor. When Al and Ti are co-modified in increments, the surface will be passivated, affecting the material capacity.
[0025] In the above-mentioned lithium cobalt oxide positive electrode material, the molar ratio of Li element, Co element and F element in the protective layer is: 0.38-1.15: 2.15-4.3: 0.38-1.15, and the cobalt source used to prepare the protective layer is cobaltous hydroxide, and the amount of cobaltous hydroxide is equivalent to 2-4wt% of the weight of the core layer.
[0026] Relatively speaking, the Li-Co-F layer in the protective layer is beneficial to resist the corrosion of the electrolyte. A small amount or excess of Co will lead to excessive Li or Co, forming byproducts of Li and Co, which will lead to cycle deterioration.
[0027] At the same time, the present invention also discloses a method for preparing the lithium cobalt oxide positive electrode material as described above, comprising the following steps:
[0028] Step 1: doping lithium cobalt oxide with magnesium oxide, yttrium oxide and zirconium oxide to obtain a core layer;
[0029] Step 2: using titanium sol and aluminum sol as raw materials, coating the shell layer on the surface of the core layer by wet coating;
[0030] Step 3: Using lithium fluoride and cobaltous hydroxide as raw materials, a lithium complex layer is prepared on the surface of the shell layer.
[0031] In the above preparation method, the step 1 is:
[0032] Cobaltous oxide, lithium carbonate, magnesium oxide, yttrium oxide and zirconium oxide are mixed, sintered and then crushed to obtain a core layer.
[0033] In the above preparation method, the step 2 is:
[0034] Adding titanium sol, aluminum sol and core layer into pure water for reaction, and then drying;
[0035] The content of Ti(OH)4 in the titanium sol is equivalent to 0.12-0.36wt% of the weight of the core layer;
[0036] The content of Al(OH)3 in the aluminum sol is equivalent to 0.145-0.435wt% of the weight of the core layer.
[0037] In the above preparation method, the step 3 is:
[0038] The product of step 2, lithium fluoride and cobaltous hydroxide are mixed and sintered to obtain a lithium cobalt oxide positive electrode material;
[0039] The lithium fluoride is equivalent to 0.1-0.3 wt% of the weight of the core layer; the cobaltous hydroxide is equivalent to 2-4 wt% of the weight of the core layer.
[0040] In the above preparation method, in step 1, sintering is carried out in two stages, the first stage is kept at 800-850°C for 3-5 hours, and the second stage is kept at 1000-1050°C for 10-14 hours;
[0041] In step 3, sintering is performed at a temperature of 900 to 950° C. for 6 to 10 hours.
[0042] Finally, the present invention also discloses the use of any of the above-mentioned lithium cobalt oxide positive electrode materials in preparing lithium ion batteries.
[0043] The beneficial effects of this application are:
[0044] The core invention of the present invention is the fast ion layer shell and the lithium composite layer; in order to reduce the impact of the fast ion layer on the core layer during the preparation process, Mg, Y, and Zr are doped in the core layer to stabilize lithium cobalt oxide, thereby avoiding the deterioration of the thermal stability of the core layer interface caused by the fast ion layer preparation process and thus affecting the cycle performance; at the same time, the lithium composite layer serves as a protective layer of the shell layer, which can reduce the interfacial side reactions under high voltage conversion conditions, so that the fast ion layer can stably realize the insertion and extraction of lithium ions, and finally achieve. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is the capacity retention rate diagram of each sample of the present invention;
[0046] Figure 2 This is a microscope photograph of Example 2 of the present invention. DETAILED DESCRIPTION
[0047] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0048] Example 1
[0049] Step 1: Cobaltous oxide and lithium carbonate were weighed at a Li / Co molar ratio of 1.08, and 0.135wt% of magnesium oxide, 0.055wt% of yttrium oxide and 0.055wt% of zirconium oxide were added (the total amount of cobaltous oxide and lithium carbonate was 100%, and the following examples and comparative examples were based on this);
[0050] The mixed materials are placed in a muffle furnace at 800-850°C for 4 hours, and then raised to 1000-1050°C for 12 hours for high-temperature sintering. After the sintering is completed, the muffle furnace is cooled naturally, and the lithium cobalt oxide (LCO) is taken out and crushed and depolymerized using a jet mill to obtain a once-crushed lithium cobalt oxide matrix (D50=4-6μm);
[0051] Step 2: Add 1.20wt% nano-scale titanium sol (Ti(OH)4, solid content: 20wt%), 1.45wt% nano-scale aluminum sol (Al(OH)3, solid content: 20wt%), and lithium cobalt oxide matrix into 5°C pure water equivalent to 100wt% of the weight of the product of step 1 in a reactor, stir for 20min, centrifuge and dry the obtained material into a drying kettle for 4h at 120°C. After sieving, the dried material is mixed with 0.2wt% lithium fluoride and 3wt% cobaltous hydroxide equivalent to the weight of the product of step 1 in a high-speed mixer for 30min to obtain a densely coated lithium cobalt oxide sample.
[0052] Step 3: Place the coated sample in a muffle furnace and sinter at 900-950°C for 8 hours. After sintering, sieve the sample with a 400-mesh sieve to obtain the final product.
[0053] Example 2
[0054] Step 1: Weigh cobalt tetroxide and lithium carbonate according to a Li / Co molar ratio of 1.08, add 0.27wt% magnesium oxide, 0.11wt% yttria and 0.11wt% zirconium oxide, mix the cobalt tetroxide, lithium carbonate and additive nano-oxide in the above formula evenly, and sinter at high temperature (sintering temperature and time are the same as in Example 1) to obtain a lithium cobalt oxide matrix.
[0055] Step 2: Add 1.20wt% nano-scale titanium sol (Ti(OH)4, solid content: 20%), 1.45wt% nano-scale aluminum sol (Al(OH)3, solid content: 20%), and lithium cobalt oxide matrix into 5°C pure water equivalent to 100wt% of the weight of the product of step 1 in a reactor, stir for 20min, centrifuge and dry the obtained material into a drying kettle for 4h at 120°C. After sieving, the dried material is mixed with 0.2wt% lithium fluoride and 3wt% cobaltous hydroxide equivalent to the weight of the product of step 1 in a high-speed mixer for 30min to obtain a densely coated lithium cobalt oxide sample.
[0056] Step 3: Place the coated sample in a muffle furnace for secondary high-temperature sintering (the sintering temperature and time are the same as in Example 1). After sintering, sieve the sample using a 400-mesh sieve to obtain the final product (reference Figure 2 ).
[0057] Example 3
[0058] Step 1: Weigh cobalt tetroxide and lithium carbonate according to a Li / Co molar ratio of 1.08, add 0.305wt% magnesium oxide, 0.165wt% yttrium oxide and 0.165wt% zirconium oxide, mix the cobalt tetroxide, lithium carbonate and additive nano-oxide in the above formula evenly, and sinter at high temperature (sintering temperature and time are the same as in Example 1) to obtain a lithium cobalt oxide matrix.
[0059] Step 2: Add 1.20wt% nano-scale titanium sol (Ti(OH)4, solid content: 20%), 1.45wt% nano-scale aluminum sol (Al(OH)3, solid content: 20%), and lithium cobalt oxide matrix into 5°C pure water equivalent to 100wt% of the weight of the product of step 1 in a reactor, stir for 20min, centrifuge and dry the obtained material into a drying kettle for 4h at 120°C. After sieving, the dried material is mixed with 0.2wt% lithium fluoride and 3wt% cobaltous hydroxide equivalent to the weight of the product of step 1 in a high-speed mixer for 30min to obtain a densely coated lithium cobalt oxide sample.
[0060] Step 3: Place the coated sample in a muffle furnace for secondary high-temperature sintering (the sintering temperature and time are the same as those in Example 1). After sintering, sieve the sample using a 400-mesh sieve to obtain the final product.
[0061] Example 4
[0062] Step 1: Weigh cobalt tetroxide and lithium carbonate according to a Li / Co molar ratio of 1.08, add 0.27wt% magnesium oxide, 0.11wt% yttria and 0.11wt% zirconium oxide, mix the cobalt tetroxide, lithium carbonate and additive nano-oxide in the above formula evenly, and sinter at high temperature (sintering temperature and time are the same as in Example 1) to obtain a lithium cobalt oxide matrix.
[0063] Step 2: Add 0.6wt% nano-scale titanium sol (Ti(OH)4, solid content: 20%) equivalent to the weight of the product of step 1, 0.725wt% nano-scale aluminum sol (Al(OH)3, solid content: 20%) equivalent to the weight of the product of step 1, and lithium cobalt oxide matrix into 5°C pure water equivalent to 100wt% of the weight of the product of step 1 in a reactor, stir for 20min, centrifuge and dry the obtained material into a drying kettle for 4h at 120°C. After sieving, the dried material is mixed with 0.2wt% lithium fluoride and 3wt% cobaltous hydroxide equivalent to the weight of the product of step 1 using a high-speed mixer for 30min to obtain a densely coated lithium cobalt oxide sample.
[0064] Step 3: Place the coated sample in a muffle furnace for secondary high-temperature sintering (the sintering temperature and time are the same as those in Example 1). After sintering, sieve the sample using a 400-mesh sieve to obtain the final product.
[0065] Example 5
[0066] Step 1: Weigh cobalt tetroxide and lithium carbonate according to a Li / Co molar ratio of 1.08, add 0.27wt% magnesium oxide, 0.11wt% yttria and 0.11wt% zirconium oxide, mix the cobalt tetroxide, lithium carbonate and additive nano-oxide in the above formula evenly, and sinter at high temperature (sintering temperature and time are the same as in Example 1) to obtain a lithium cobalt oxide matrix.
[0067] Step 2: Add 1.8wt% of nano-scale titanium sol (Ti(OH)4, solid content: 20%), 2.175wt% of nano-scale aluminum sol (Al(OH)3, solid content: 20%), and lithium cobalt oxide matrix into 5°C pure water equivalent to 100wt% of the weight of the product of step 1 in a reactor, stir for 20min, centrifuge and dry the obtained material into a drying kettle for 4h at 120°C. After sieving, the dried material is mixed with 0.2wt% of lithium fluoride and 3wt% of cobaltous hydroxide, equivalent to the weight of the product of step 1, using a high-speed mixer for 30min to obtain a densely coated lithium cobalt oxide sample.
[0068] Step 3: Place the coated sample in a muffle furnace for secondary high-temperature sintering (the sintering temperature and time are the same as those in Example 1). After sintering, sieve the sample using a 400-mesh sieve to obtain the final product.
[0069] Example 6
[0070] Step 1: Weigh cobalt tetroxide and lithium carbonate according to a Li / Co molar ratio of 1.08, add 0.27wt% magnesium oxide, 0.11wt% yttria and 0.11wt% zirconium oxide, mix the cobalt tetroxide, lithium carbonate and additive nano-oxide in the above formula evenly, and sinter at high temperature (sintering temperature and time are the same as in Example 1) to obtain a lithium cobalt oxide matrix.
[0071] Step 2: Add 1.8wt% of nano-scale titanium sol (Ti(OH)4, solid content: 20%), 2.175wt% of nano-scale aluminum sol (Al(OH)3, solid content: 20%), and lithium cobalt oxide matrix into 5°C pure water equivalent to 100wt% of the weight of the product of step 1 in a reactor, stir for 20min, centrifuge and dry the obtained material into a drying kettle for 4h at 120°C. After sieving, the dried material is mixed with 0.1wt% of lithium fluoride and 3wt% of cobaltous hydroxide equivalent to the weight of the product of step 1 in a high-speed mixer for 30min to obtain a densely coated lithium cobalt oxide sample.
[0072] Step 3: Place the coated sample in a muffle furnace for secondary high-temperature sintering (the sintering temperature and time are the same as those in Example 1). After sintering, sieve the sample using a 400-mesh sieve to obtain the final product.
[0073] Example 7
[0074] Step 1: Weigh cobalt tetroxide and lithium carbonate according to a Li / Co molar ratio of 1.08, add 0.27wt% magnesium oxide, 0.11wt% yttria and 0.11wt% zirconium oxide, mix the cobalt tetroxide, lithium carbonate and additive nano-oxide in the above formula evenly, and sinter at high temperature (sintering temperature and time are the same as in Example 1) to obtain a lithium cobalt oxide matrix.
[0075] Step 2: Add 1.8wt% of nano-scale titanium sol (Ti(OH)4, solid content: 20%), 2.175wt% of nano-scale aluminum sol (Al(OH)3, solid content: 20%), and lithium cobalt oxide matrix into 5°C pure water equivalent to 100wt% of the weight of the product of step 1 in a reactor, stir for 20min, centrifuge and dry the obtained material into a drying kettle for 4h at 120°C. After sieving, the dried material is mixed with 0.3wt% of lithium fluoride and 3wt% of cobaltous hydroxide, equivalent to the weight of the product of step 1, using a high-speed mixer for 30min to obtain a densely coated lithium cobalt oxide sample.
[0076] Step 3: Place the coated sample in a muffle furnace for secondary high-temperature sintering (the sintering temperature and time are the same as those in Example 1). After sintering, sieve the sample using a 400-mesh sieve to obtain the final product.
[0077] Example 8
[0078] The method is substantially the same as Example 2, except that the amount of cobaltous hydroxide used is 2 wt %.
[0079] Example 9
[0080] The method is substantially the same as Example 2, except that the amount of cobaltous hydroxide used is 4 wt %.
[0081] Comparative Example 1
[0082] The process is substantially the same as in Example 2, except that the amount of the additive nano-oxide is adjusted to 0wt% magnesium oxide, 0wt% yttrium oxide and 0% zirconium oxide, and the rest is the same as in Example 2.
[0083] Comparative Example 2
[0084] Basically the same as Example 2, the amount of coating additives added is adjusted to 0wt% nano-grade titanium sol (Ti(OH)4, solid content: 20%), 0wt% nano-grade aluminum sol (Al(OH)3, solid content: 20%), and the rest is the same as Example 2.
[0085] Comparative Example 3
[0086] Basically the same as Example 2, the amount of coating additive added is adjusted to 0wt% lithium fluoride, and the rest is the same as Example 2.
[0087] Comparative Example 4
[0088] The process is substantially the same as in Example 2, except that the amount of the coating additive added is adjusted to 1 wt % of cobaltous hydroxide, and the rest is the same as in Example 2.
[0089] Comparative Example 5
[0090] The process is substantially the same as in Example 2, except that the amount of the coating additive added is adjusted to 5 wt % of cobaltous hydroxide, and the rest is the same as in Example 2.
[0091] Comparative Example 6
[0092] It is substantially the same as Example 2, except that the amounts of doping substances used are: 0.27wt% magnesium oxide, 0wt% yttrium oxide and 0.22wt% zirconium oxide.
[0093] Comparative Example 7
[0094] It is substantially the same as Example 2, except that the amounts of doping substances used are: 0.27wt% magnesium oxide, 0.22wt% yttrium oxide and 0wt% zirconium oxide.
[0095] Comparative Example 8
[0096] It is substantially the same as Example 2, except that the amounts of doping substances used are: 0wt% magnesium oxide, 0.24wt% yttrium oxide and 0.24wt% zirconium oxide.
[0097] Comparative Example 9
[0098] The method is substantially the same as Example 2, except that dry coating is adopted.
[0099] The method is specifically as follows:
[0100] Step 1: Weigh cobalt tetroxide and lithium carbonate in a Li / Co molar ratio of 1.08, add 0.27wt% magnesium oxide, 0.11wt% yttria and 0.11wt% zirconium oxide in total amount of cobalt tetroxide and lithium carbonate, mix the cobalt tetroxide with lithium carbonate and the additive nano-oxide in the above formula evenly, and sinter at high temperature (sintering temperature and time are the same as in Example 1) to obtain a lithium cobalt oxide matrix.
[0101] Step 2: Add 0.17wt% of nano-sized titanium compound (TiO2) and 0.21wt% of nano-sized aluminum compound (Al2O3) to the lithium cobalt oxide matrix and mix them together with the lithium cobalt oxide matrix using a high-speed mixer for 30 minutes to obtain a densely coated lithium cobalt oxide sample.
[0102] Step 3: Place the coated and secondary mixed sample in a muffle furnace for secondary high-temperature sintering (the sintering temperature and time are the same as those in Example 1). After sintering, sieve the sample using a 400-mesh sieve to obtain a secondary material.
[0103] Step 4: Add 0.2wt% lithium fluoride and 3wt% cobaltous hydroxide to the lithium cobalt oxide matrix and mix with the lithium cobalt oxide secondary material using a high-speed mixer for 30 minutes to obtain a densely coated lithium cobalt oxide sample.
[0104] Step 5: Place the three mixed samples after coating into a muffle furnace and sinter them at high temperature for three times (the sintering temperature and time are the same as those in Example 1). After sintering, sieve the sample with a 400-mesh sieve to obtain a finished product.
[0105] Comparative Example 10
[0106] The method is substantially the same as Example 2, except that in step 2, the titanium source, the aluminum source, lithium fluoride and cobaltous hydroxide are mixed and dry-coated.
[0107] The method is specifically as follows:
[0108] Step 1: Weigh cobalt tetroxide and lithium carbonate in a Li / Co molar ratio of 1.08, add 0.27wt% magnesium oxide, 0.11wt% yttria and 0.11wt% zirconium oxide in total amount of cobalt tetroxide and lithium carbonate, mix the cobalt tetroxide with lithium carbonate and the additive nano-oxide in the above formula evenly, and sinter at high temperature (sintering temperature and time are the same as in Example 1) to obtain a lithium cobalt oxide matrix.
[0109] Step 2: Add 0.17wt% of nano-sized titanium compound (TiO2), 0.21wt% of nano-sized aluminum compound (Al2O3), 0.2wt% of lithium fluoride and 3wt% of cobaltous hydroxide to the lithium cobalt oxide matrix material and mix them with a high-speed mixer for 30 minutes to obtain a densely coated lithium cobalt oxide sample.
[0110] Step 3: Place the coated and secondary mixed sample in a muffle furnace for secondary high-temperature sintering (the sintering temperature and time are the same as those in Example 1). After sintering, sieve the sample using a 400-mesh sieve to obtain a finished product.
[0111] Test part:
[0112] The positive electrode material, conductive agent acetylene black and binder PVDF were weighed in a mass ratio of 92:4:4, and mixed with dispersant N-methylpyrrolidone (NMP) to form a slurry, which was then coated on the current collector aluminum foil, and then dried at 120°C and cut into 1.56cm2 circular positive electrode sheets. The metal lithium sheet was used as the negative electrode, combined with the separator, the above positive electrode sheet, and LiPF6 (EC:DEC=1:1) electrolyte, and assembled into a 2016 button cell in a glove box. The constant current charge and discharge test was performed on the Xinwei battery test system. Test conditions: 1C rate, 50 cycles, voltage range 3.0-4.65V.
[0113] The test results refer to Table 1;
[0114] Table 1 Test results
[0115] 0.1C Premiere First effect 45℃-1C-50 cycles retention rate Example 1 197.8 93.3 88.3% Example 2 198.1 93.4 89.0% Example 3 198.5 93.3 88.7% Example 4 198.2 93.3 88.6% Example 5 197.9 93.2 88.4% Example 6 197.5 93.3 88.7% Example 7 198.5 93.4 88.2% Example 8 197.8 93 88.06% Example 9 196.9 93.9 87.79% Comparative Example 1 197.6 93.0 75.3% Comparative Example 2 197.9 93.2 84.1% Comparative Example 3 194.4 93.1 85.5% Comparative Example 4 196.9 93.4 85.7% Comparative Example 5 196.9 93.4 84.7% Comparative Example 6 197.2 93.3 85.35% Comparative Example 7 197.4 93.3 84.66% Comparative Example 8 197.5 93.3 83.59% Comparative Example 9 197 93.4 85.68% Comparative Example 10 196.8 93.4 85.47%
[0116] The capacity retention rates of different samples can be found in Figure 1 ;pass Figure 1 It can be seen that all the examples are located in a concentrated area, and all the other comparative examples are located in other areas except comparative example 1. The circulation retention effect of comparative example 1 is the worst.
[0117] In Examples 1-9 using the present technology, the cycle retention rates of 1C cycles for 50 weeks at a cut-off voltage of 4.65V in a high temperature test at 45°C are better than those of Comparative Examples 1-5, and Example 2 has the best performance.
[0118] Based on the principle analysis, comparing Examples 1-3, in Example 1, the addition of doping elements is missing during the primary sintering process, resulting in the positive electrode material not having a relatively stable structure. During the wet coating process, it is not resistant to water washing, resulting in easy collapse of the structure, which is ultimately manifested in the deterioration of the cycle performance.
[0119] In the wet coating process, the comparative example 2 lacks the addition of nano-scale sol compounds, which is not conducive to forming a stable and reliable shell coating layer, resulting in an unstable outer layer structure and ultimately causing deterioration of the cycle performance.
[0120] Compared with Example 2, Comparative Example 3 reduces the addition of LiF, and no Li-Co-F lithium complex is formed on the surface, resulting in the material having a capacity far lower than that of the embodiment during the first discharge process. At the same time, the instability of the outer layer of the shell aggravates the side reactions of the cycle process, resulting in deterioration of the cycle performance.
[0121] Compared with Example 2, Comparative Examples 4 and 5 reduce the amount of cobaltous hydroxide added, indicating that too much or too little cobaltous hydroxide will affect the thickness of the coating shell layer, and too much or too little coating will also affect the electrochemical performance. Too thin a coating layer will lead to instability of the coating layer, and too thick a coating layer will lead to excessive coating, resulting in deterioration of the cycle.
[0122] Compared with Example 2, the cycle performance of Comparative Examples 1, 6, 7, and 8 becomes worse as the doping elements are reduced. The ion radius of Y is larger, which can increase the diffusion channel of lithium ions and is beneficial to the transmission of lithium ions. Mg and Zr doping can play a "pillar role" to reduce lattice distortion, stabilize the crystal structure, and improve electrical conductivity. Compared with Comparative Example 1, Mg-Zr, Mg-Y, and Y-Zr co-doping can improve the cycle performance, and Mg-Y-Zr co-doping can further improve the cycle performance.
[0123] Compared with Example 2, Comparative Example 9 used dry coating when forming the fast ion layer, which shows that the fast ion layer formed by dry coating is unstable and uneven, which eventually leads to cycle deterioration.
[0124] Compared with Example 2, Comparative Example 10 uses dry coating to simultaneously coat the fast ion layer and the fluoride, with the aim of sintering the finished product in one step during the secondary sintering. Due to the use of dry coating, the fast ion layer formed is unstable and uneven, and the instability of the fast ion layer and the fluoride protective layer ultimately leads to cycle deterioration.
[0125] The key control points of this technology are as follows: 1. Appropriate doping elements stabilize the Mg-Y-Zr structure of the inner core layer; 2. Add an appropriate amount of coating agent by wet coating to form a stable shell Co-Al-Ti-O spinel phase during the sintering process, which is also helpful for the release and entry of lithium ions; 3. The outer shell forms a Li-Co-F lithium complex to provide capacity; 4. An appropriate amount of cobaltous hydroxide is added to form a uniform coating shell layer to isolate the lithium cobalt oxide from direct contact with the electrolyte and reduce interface side reactions under high voltage.
Claims
1. A lithium cobalt oxide positive electrode material, characterized in that: It includes a core layer, a shell layer, and a protective layer arranged in sequence from the inside to the outside; The core layer is a core layer made of lithium cobalt oxide doped with Mg, Y and Zr; The shell layer is a fast ion layer of spinel phase composed of Co, Al, Ti and O elements; The protective layer is a lithium composite layer composed of Li, Co and F elements; The core layer contains 0.135-0.305wt% magnesium oxide, 0.055-0.165wt% yttrium oxide and 0.055-0.165wt% zirconium oxide equivalent to the weight of lithium cobalt oxide; The molar ratio of Al element to Ti element in the fast ion layer is 0.9-2.7:0.5-1.55; The molar ratio of Li element, Co element and F element in the protective layer is: 0.38-1.15: 2.15-4.3: 0.38-1.
15. The cobalt source used to prepare the protective layer is cobaltous hydroxide, and the amount of cobaltous hydroxide is equivalent to 2-4wt% of the weight of the core layer. The fast ion layer is made of titanium sol and aluminum sol, and is coated with a shell layer on the surface of the core layer by a wet coating method to form a fast ion layer.
2. A method for preparing the lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The steps include: Step 1: doping lithium cobalt oxide with magnesium oxide, yttrium oxide and zirconium oxide to obtain a core layer; Step 2: using titanium sol and aluminum sol as raw materials, coating the shell layer on the surface of the core layer by wet coating; Step 3: Using lithium fluoride and cobaltous hydroxide as raw materials, a lithium complex layer is prepared on the surface of the shell layer.
3. The preparation method according to claim 2, characterized in that: The step 1 is: Cobaltous oxide, lithium carbonate, magnesium oxide, yttrium oxide and zirconium oxide are mixed, sintered and then crushed to obtain a core layer.
4. The preparation method according to claim 2, characterized in that: The step 2 is: Adding titanium sol, aluminum sol and core layer into pure water for reaction, and then drying; The content of Ti(OH)4 in the titanium sol is equivalent to 0.12-0.36wt% of the weight of the core layer; The content of Al(OH)3 in the aluminum sol is equivalent to 0.145-0.435wt% of the weight of the core layer.
5. The preparation method according to claim 2, characterized in that: The step 3 is: The product of step 2, lithium fluoride and cobaltous hydroxide are mixed and sintered to obtain a lithium cobalt oxide positive electrode material; The lithium fluoride is equivalent to 0.1-0.3 wt% of the weight of the core layer; the cobaltous hydroxide is equivalent to 2-4 wt% of the weight of the core layer.
6. The preparation method according to claim 5, characterized in that: In step 1, sintering is performed in two stages, the first stage is kept at 800-850° C. for 3-5 hours, and the second stage is kept at 1000-1050° C. for 10-14 hours; In step 3, sintering is performed at a temperature of 900 to 950° C. for 6 to 10 hours.
7. Use of the lithium cobalt oxide positive electrode material as claimed in claim 1 in preparing lithium ion batteries.
Citation Information
Patent Citations
Coated modified lithium cobalt oxide positive electrode material, preparation method thereof and lithium ion battery
CN118458839A
Alcoholic titanium aluminum sol-coated lithium ion battery multi-element composite positive electrode material, and preparation method and application thereof
CN110176581A
Surface-coated lithium ion battery positive electrode material and preparation method thereof
CN113707851A
Cited By
Method for detecting content of impurity cobaltosic oxide in lithium cobalt oxide
CN122193197A